2023
DOI: 10.1186/s12872-023-03136-8
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal association between N-terminal B-type natriuretic peptide, anxiety and social support in patients with HFpEF: results from the multicentre randomized controlled Aldo-DHF trial

Abstract: Background Higher plasma levels of natriuretic peptides (NPs) have been associated with reduced anxiety in experimental research and a number of patient samples. As NP levels are elevated in heart failure patients, we investigate whether this elevation is related to anxiety in patients with heart failure with preserved ejection fraction (HFpEF). Methods Post-hoc regression and mediation analyses were conducted, using data of 422 patients with HFpEF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“… 27 , 28 , 29 Furthermore, anxiety disorders may elevate the risk of cardiac dysfunction and adverse outcomes by potentially impeding the cardioprotective effects of vagus‐mediated B‐type natriuretic peptide (BNP). 30 These findings collectively support a plausible connection between anxiety disorders and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 66%
“… 27 , 28 , 29 Furthermore, anxiety disorders may elevate the risk of cardiac dysfunction and adverse outcomes by potentially impeding the cardioprotective effects of vagus‐mediated B‐type natriuretic peptide (BNP). 30 These findings collectively support a plausible connection between anxiety disorders and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 66%
“…In HFpEF, additional stuff is put into the heart because of the increased wall stress and impaired diastolic filling and, subsequently, the release of BNP and ANP [77]. These peptides induce vasodilation and natriuresis, and their blood levels reflect the poorer the patientʹs heart function and higher risk for adverse cardiac remodeling [78]. A study has shown that natriuretic peptide levels had high diagnostic accuracy for discriminating HFpEF from other causes of breathlessness.…”
Section: Natriuretic Peptides Releasementioning
confidence: 99%